(untitled) (Global Journal of Science Frontier Research, 2018)
Nano-structured thin films of cadmium sulfide (CdS) have been wet chemically deposited on soda lime glass substrate and, fluorine-doped tin oxide (FTO) coated conducting glass substrates by using non-ionic surfactant; Hexamethylenetetramine (HMTA). The structural, optical and surface morphological properties of the CdS films was investigated through the analysis of the x-ray diffraction, optical spectroscopy and, scanning electron microscopy. The structural and optical study showed that the CdS thin films are polycrystalline in nature having cubic crystal structure. The optical study revealed that the CdS films have a direct band gap energy of 2.44 eV. The SEM images show interconnected nano-plates like morphology with a well-defined surface area. Finally, the photoelectrochemical (PEC) performance of HMTA mediated CdS thin film samples were studied. The CdS based solar cell shows PEC performance with maximum short circuit current density of (I sc ) 1.25 mA/cm 2 .